The Typology of the Providential Leader in the Modern Romanian Political Imaginary - MITU, Sorin (Studia Universitatis Babeș-Bolyai Historia, 2019)
In this paper, we will attempt to provide an overview of the typology of the providential leader in the Romanian political culture. The providential ruler is a political myth which gives meaning to modern societies, divided along the fault lines of diverging economic interests and ideological beliefs. We propose a classification centred on the symbolic functions exercised by the political figures. The Saviour, the Martyr, the Vigilante and the Constructor are the four mythical constellations that can adequately structure the specific roles played by the Romanian providential leaders. Rezumat: Tipologia conducătorilor providenţiali în imaginarul politic român modern. În acest studiu vom încerca să schiţăm o imagine de ansamblu asupra tipologiei liderilor salvatori din cadrul culturii politice româneşti. Conducătorul providenţial este un mit politic, care dă sens unor societăţi moderne, divizate de-a lungul liniilor de falie ale unor interese economice şi credinţe politice divergente. Vom propune o clasificare centrată pe funcţiile simbolice exercitate de personajele politice. Salvatorul, Martirul, Justiţiarul şi Constructorul sunt cele patru constelaţii mitice care pot să structureze în mod adecvat rolurile specifice jucate de conducătorii providenţiali români. Cuvinte-cheie: imaginar politic, România modernă, conducător providenţial, bazin semantic, propagandă.